The Benefits and challenges of virtual reality application in rehabilitation for chronic conditions - Kraśnik, Wojciech; Jankowska, Olga; Kurzeja, Jacek; Piotrowicz, Katarzyna; Piotrowicz, Hubert; Bajkacz, Agnieszka; Rogala, Anna; Osmólska, Joanna (Journal of Education, Health and Sport, 2024)
The recent era of rapid advancements in information technology has enabled various medical disciplines to tackle longstanding problems in novel ways. Among these, virtual reality (VR) has emerged as a promising alternative or complement to conventional physical therapy (CPT) for managing chronic musculoskeletal, degenerative, neurological, and pulmonary conditions. Increased patient motivation during treatment, low drop-out rates, and instant feedback are among the primary reasons VR is gaining trust among physicians, patients, and caregivers worldwide. Evidence suggests that VR can significantly enhance motor performance, cognitive skills, pulmonary function, activities of daily living (ADLs), quality of life (QoL), and even reduce pain intensity in several chronic diseases. Notably, patients with stroke, Parkinson’s disease, multiple sclerosis (MS), and chronic obstructive pulmonary disease (COPD) are poised to be the primary beneficiaries of VR. Thus, it appears that VR-based techniques are set to leave a footprint on clinical practice globally. However, challenges to the clinical adoption of VR remain, including technical limitations, the lack of standardized guidelines, and minor safety concerns that must be addressed. This paper summarizes the background, current developments, and key considerations for future research in this rapidly evolving field.